How scale and ownership are related to financial performance? A productivity analysis of the Chinese banking sector - Carlos Barros; Hidemichi Fujii; Shunsuke Managi (Journal of Economic Structures, 2015)
This paper analyzes productivity with a directional distance function model by investigating convexity and non-convexity in the Chinese banking sector. Two primary findings are summarized. First, there is a distinct change in productivity between large versus small banks and public versus nationwide joint-stock banks; the economies of scale and public orientation of the Chinese economy affect the performance of nationwide joint-stock banks. Second, the number of banks that experience local versus global technological change is small, indicating that productivity changes are driven by national rather than regional dynamics, although minor regional dynamics exist in the data.
Keywords: G21; G32; O47; 330; Productivity change; Ownership; Scale; Directional distance function; Chinese banking firms